Potential and promotion of Rabi castor cultivation through drip-fertigation in southern India: Potential and promotion of Rabi castor cultivation through drip-fertigation in southern India - G SURESH; S N SUDHAKARA BABU; S R VENKATACHALAM; G D SATISH KUMAR; C LAVANYA (Journal of Oilseeds Research, 2023)
Raising castor during winter (rabi) season with assured drip-irrigation using hybrids is a new dimension with promise that provides greater stability and higher productivity and avoids many problems of kharif castor. It is prudent to expand castor during rabi with limited irrigations in southern India especially in Telangana, Andhra Pradesh and parts of Tamil Nadu.